Learning Curve and Initial Outcomes of Full-Endoscopic Posterior Lumbar Interbody Fusion - Tan, Renchun; Lv, Xin; Wu, Pengfei; Li, Yawei; Dai, Yuliang; Jiang, Bin; Ren, Bolin; Lv, Guohua; Wang, Bing (Frontiers in Surgery, 2022)
Study Design This was a retrospective cohort study. Objective We evaluated the feasibility, safety, and accuracy of full-endoscopic posterior lumbar interbody fusion (FE-PLIF) by assessing the learning curve and initial clinical outcomes. Summary of Background Data Low back pain is one of the crucial medical conditions worldwide. FE-PLIF has been reported to be a minimally invasive method to treat mechanical low back pain, but there lacks a thorough evaluation on this new technique. Methods The patients were divided into three groups in the order of operating date, implying that Group A consisted of the initial 12 cases, Group B the subsequent 12 cases, and Group C the last 12 cases. The data of patients were reviewed for gender, age, preoperative symptoms, satisfaction, as well as clinical outcomes demonstrated by visual analog scale (VAS). The operative time and intraoperative fluoroscopy were recorded to demonstrate the learning curve and the extent of radiographic exposure. Statistical significance was set at a p < 0.05 (two-sided). Results The patients enrolled in this study were followed up at an average of 1.41 ± 0.24 years. Overall, patients were satisfied with the surgery. The average number of intraoperative fluoroscopy was 6.97 ± 0.74. A significant improvement was observed in the VAS of both lumbar pain and leg pain. The overall fusion rate was 77.7%. Complications were reported in two patients in Group A, one in Group B, and none in Group C. The average operative time showed a trend of gradual decline. The learning curve was characterized using a cubic regression analysis as y = –27.07x + 1.42x2–0.24x3 + 521.84 (R2 = 0.617, p = 0.000). Conclusions FE-PLIF is an effective and safe method for treating low back pain caused by short-segmental degenerative diseases. The learning curve of this technique is steep at the initial stage but acceptable and shows great potential for improvement.